37 A centralised inter-facility patient transfer service in southern finland -the helsinki experience. (16th April 2018) - Stenius, F; Holmström, P; Etelä, J; Sarvikivi, K; Puolakka, T
Abstract : Aim: Inter-facility patient transfers form an important share of out-of-hospital patient transport. In many countries these transfers are commonly done by small ambulance companies and by the local emergency medical services. The aim of this observational study was to report the operation of the only centralised inter-facility transfer service in Finland. Method: Helsinki University Hospital patient transfer service is responsible of all inter-facility transfers in the region with 1.6 million inhabitants. During a three-month cohort (1.9–31.11.2016) all patients transferred by the transfer service ambulances were selected for the study. The patient reports were collected and quality deviations during transport were registered based on predetermined criteria. Results: In a total of 3034 transfers, lights and sirens were required in 73 (2.4%) cases. In 45 (1.5%) transfers the patient was accompanied by a physician and in 35 (1.1%) a nurse from the referring hospital. The most common issues requiring treatment during transport were pain (numeric rating scale ≥4) in 191 (6.3%) and hypoxemia in 119 (3.9%) transfers. Moreover, 147 (4.8%) patients carried microbes important for hospital hygiene. Quality deviations were registered in 338 transfers (8.4%). The most common deviations were insufficient or missing written reporting in 244/338 cases (72.2%). Problems were also encountered with patient monitoring and treatment in 80/338 transfers (23.7%). Adverse events were registered during 16 transfers (0.5%). Conclusion: In daily inter-facility transfer service operations, the need for lights and sirens was uncommon. Acute pain and hypoxemia were the most common issues to be addressed during transport. Adverse events were rare. Conflict of interest: None Funding: None